Effect of naringin on hemodynamic changes and left ventricular function in renal artery occluded renovascular hypertension in rats - Asjad Visnagri; Mohammad Adil; Amit D Kandhare; Subhash L Bodhankar (Wolters Kluwer Medknow Publications, 2015)
Background: Renal artery occlusion (RAO) induced hypertension is a major health problem associated with structural and functional variations of the renal and cardiac vasculature. Naringin a flavanone glycoside derived possesses metal-chelating, antioxidant and free radical scavenging properties. Objective: The objective of this study was to investigate the antihypertensive activity of naringin in RAO induced hypertension in rats.Material and Methods: Male Wistar rats (180-200 g) were divided into five groups Sham, RAO, naringin (20, 40 and 80 mg/kg). Animals were pretreated with naringin (20, 40 and 80 mg/kg p.o) for 4 weeks. On the last day of the experiment, left renal artery was occluded with renal bulldog clamp for 4 h. After assessment of hemodynamic and left ventricular function various biochemical (superoxide dismutase [SOD], glutathione [GSH] and malondialdehyde [MDA]) and histological parameters were determined in the kidney. Results: RAO group significantly (P < 0.001) increased hemodynamic parameters at 15, 30 and 45 min of clamp removal. Naringin (40 and 80 mg/kg) treated groups showed a significant decrease in hemodynamic parameters at 15 min. after clamp removal that remained sustained for 60 min. Naringin (40 and 80 mg/kg) treated groups showed significant improvement in left ventricular function at 15, 30 and 45 min after clamp removal. Alteration in level of SOD, GSH and MDA was significantly restored by naringin (40 and 80 mg/kg) treatment. It also reduced histological aberration induced in kidney by RAO. Conclusion: It is concluded that the antihypertensive activity of naringin may result through inhibition of oxidative stress.